Perbandingan MAPE Metode Arima dan FTS Chen pada Peramalan Harga Minyak Mentah Widuri di Indonesia - Ikhtiyar, Zakaria Bani; Sulistijanti, Wellie; Sari, Silvia Novita; Mahiruna, Adiyah (UIN Walisongo Semarang, 2024)
The need for crude oil greatly affects economic activities on a micro and macro scale. Indonesia is one of the countries that produces crude oil, although the amount produced is not as large as countries in the Middle East. The global price of crude oil has a direct impact on Indonesia's rising fuel prices. To find out the world price of crude oil in the future, forecasting can be done. Widuri type crude oil is one of the crude oils that is a priority in Indonesia. This study compares the accuracy of forecasting the price of Widuri type crude oil with the MAPE accuracy calculation method and the forecasting method compared is the ARIMA method with the FTS Chen method.Keywords: forecasting, Oil, ARIMA, Fuzzy Time Series (FTS) Chen.